2019
DOI: 10.3390/ijerph16183455
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of PM10 from Industrial Point Sources in a Rural Area in Limpopo, South Africa

Abstract: Air pollution from industrial point sources accounts for a large proportion of air pollution issues affecting many communities around the world. However, emissions from these sources are technically controllable by putting in place abatement technologies with feasible and stringent regulatory conditions in the operation licenses. Pollution from other sources such as soil erosion, forest fires, road dust, and biomass burning, are subject to several unpredictable natural or economic factors. In this study, findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Cases of CEV in the younger, as well as the older generation, is still an issue that requires continuous monitoring and intervention. A recent study in Limpopo, South Africa with similar results, (Tshehla & Wright, 2019b) has suggested a revision of the current South Africa PM₁₀ standards to be comparable to the WHO guidelines. This is desirable to improve the protection of human health and wellbeing.…”
Section: Residents Perceptions and Complaintsmentioning
confidence: 71%
“…Cases of CEV in the younger, as well as the older generation, is still an issue that requires continuous monitoring and intervention. A recent study in Limpopo, South Africa with similar results, (Tshehla & Wright, 2019b) has suggested a revision of the current South Africa PM₁₀ standards to be comparable to the WHO guidelines. This is desirable to improve the protection of human health and wellbeing.…”
Section: Residents Perceptions and Complaintsmentioning
confidence: 71%
“…Carbonaceous aerosols cause more concern due to their complex impact on human health (Tshehla and Wright, 2019) and environment (Peng et al, 2019;Wu et al, 2019). EC has strong absorptivity of solar radiation and is considered to be the most important particulate component related to global warming, whereas OC is mainly a scattering medium and exerts a negative relation forcing effect (Ramirez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Modelling has been often used to evaluate concentration and dispersion process of pollutants in air [9], water [10] and ground [11]. In the modeling field there are various mathematical approaches to describe reality and to define the behavior of solid particles such as particulates, such as discrete element method (DEM) [12].…”
Section: Introductionmentioning
confidence: 99%